2009
DOI: 10.1159/000235796
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetics in Delirium in the Elderly Patient

Abstract: Delirium is an important neuropsychiatric syndrome in the elderly that is associated with an increase in mortality, impaired physical and cognitive recovery, and increased healthcare costs. Two important gaps in daily practice with delirium are the pathophysiological obscurity and the low recognition rates. Genetics offers the possibility to contribute knowledge to both of these gaps with its unique and diverse techniques. However, genetic studies in delirium have been scarce until recently, due to the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 90 publications
0
32
0
2
Order By: Relevance
“…34 Previous observations suggest that inflammatory markers, especially the microglial markers CD68 and HLA-DR, show higher activity in two of the most important predisposing factors for delirium, i.e., higher age and cognitive impairment. 14,35 The question emerges whether this relationship between delirium and a higher level of inflammation in the brain can be attributed solely to the prior activation of microglia in the brain associated with these predisposing factors for delirium.…”
Section: Figmentioning
confidence: 99%
“…34 Previous observations suggest that inflammatory markers, especially the microglial markers CD68 and HLA-DR, show higher activity in two of the most important predisposing factors for delirium, i.e., higher age and cognitive impairment. 14,35 The question emerges whether this relationship between delirium and a higher level of inflammation in the brain can be attributed solely to the prior activation of microglia in the brain associated with these predisposing factors for delirium.…”
Section: Figmentioning
confidence: 99%
“…Furthermore, we selected these five SNPs because they have been found before in studies in association with diseases, which makes functionality probable. However, we have not investigated the entire gene, so we could have missed certain (unknown) SNPs that are associated with delirium [40].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the utilization of a haplotype analysis including other candidate genes to assess functional synergistic effects could be promising [28]. However, genetic research in delirium is only starting and large cohorts for reliable validation are not yet available [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies into dopamine-related genes in delirium in elderly patients are scarce, although these studies could offer a promising contribution to the knowledge of the pathophysiology [10]. Former studies showed that the SLC6A3 gene (rs393795) and possibly the DRD2 gene (rs6276) were associated with delirium [11].…”
Section: Introductionmentioning
confidence: 99%